Renewing Islamic Educational Management: An Analysis of Qur’anic Principles in Tafsir Al-Misbah - Sofyan Puji Pranata; Muhammad Irfan; Syaiful Kiram; Nistia Sri Utari; Syahmirwan (Jurnal test, 2025)
This article explores the foundational principles of Islamic educational management through the Qur’anic interpretations of Tafsir Al-Misbah by M. Quraish Shihab. Responding to the contemporary challenges of globalization and the urgency to ground education in Qur’anic values, the study employs a library research method with a descriptive-qualitative approach. The analysis focuses on three key principles: justice (Q.S. Ar-Rahman: 7–9), sincerity (Q.S. Al-Bayyinah: 5), and trustworthiness (Q.S. An-Nisa’: 58). The findings indicate that justice ensures equity and inclusivity in managing educational resources and policies; sincerity provides a moral and spiritual foundation that enhances dedication and integrity; while trustworthiness underscores accountability in leadership and the fulfillment of responsibilities. The study not only enriches theoretical discourse by offering a tafsir-based framework for Islamic educational management but also provides practical implications for shaping institutional vision, mission, and governance in alignment with Islamic values.